2008
DOI: 10.1243/09576509jpe471
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic effects of blade sweep and skew in low-speed axial flow rotors at the design flow rate: An overview

Abstract: A detailed literature survey is presented herein in order to overview the aerodynamic impact of non-radial blade stacking techniques applied to axial flow fan and compressor rotors. The literature suggests a consensus that forward blade sweep and skew provides a means for the following advantages in the part load operational range of low-speed axial flow turbofan and compressor rotors: improvement of efficiency and performance, and extension of stall-free operating range. However, the published research result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 34 publications
4
56
0
Order By: Relevance
“…It is illustrated that the front loading near the tip is decreased with the enlarged sweep angle, while that near the hub is increased. Because the front of main blade locates at the axial part of the impeller, the loading redistribution effect is similar with that in the axial case [12]. Such effect is also reported in a former centrifugal case [25], but the extent in the current case is much stronger due to the significant change of sweep angle.…”
Section: Effect On the Front Loadingsupporting
confidence: 71%
See 1 more Smart Citation
“…It is illustrated that the front loading near the tip is decreased with the enlarged sweep angle, while that near the hub is increased. Because the front of main blade locates at the axial part of the impeller, the loading redistribution effect is similar with that in the axial case [12]. Such effect is also reported in a former centrifugal case [25], but the extent in the current case is much stronger due to the significant change of sweep angle.…”
Section: Effect On the Front Loadingsupporting
confidence: 71%
“…Its application has been widely spread from compressors to turbines and from rotors to stators [10], especially applied to blade ends to improve the endwall flowfields [11]. For compressor rotors, a detailed survey [12] suggested that forward swept blades improved the efficiency and extended the stall-free operating range by reducing the near-wall and tip clearance losses, as well as controlling the secondary flows and radial migration of high-loss fluid. More recently, Okui et al [13] optimized the sweep feature, the camber line and the chord length of a transonic axial compressor rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy of sound reduction involves the installation of endplates at the blade tip (see Figure 8) to modify the behavior of the leakage flow and the related vortical structure [52]. Apart from the acoustic interests, the effects of forward-swept designs on the performance and efficiency of fans with non-free-vortex blades have then been investigated by Corsini and Rispoli [53] and Vad [54,55]. These authors respectively highlighted the advantages of swept blades into providing an extension of the stall margin and to obtain an efficiency gain in case of rotors designed with NFV techniques featuring positive gradients of circulation along the radius.…”
Section: -2010 Analytic Design and Cfd Optimizationmentioning
confidence: 99%
“…Aerodynamics of sweep blade had been investigated and analyzed by many researchers [2][3][4][5]. Results by Li et al [2], Vad [4], and McNulty et al [5] show that sweep blade can improve the aerodynamics performance of fans and compressors, including increasing total-pressure peak value, enhancing efficiency, and widening no-stall range.…”
Section: Introductionmentioning
confidence: 99%
“…Results by Li et al [2], Vad [4], and McNulty et al [5] show that sweep blade can improve the aerodynamics performance of fans and compressors, including increasing total-pressure peak value, enhancing efficiency, and widening no-stall range. By both CFD simulations and experiments, Gallimore et al [1,3] investigated sweep blade in hi-speed axial compressors.…”
Section: Introductionmentioning
confidence: 99%